2020
DOI: 10.1007/s00198-020-05285-4
|View full text |Cite
|
Sign up to set email alerts
|

Low bone mineral density is associated with hypogonadism and cranial irradiation in male childhood cancer survivors

Abstract: We investigated if bone mineral density was related to testosterone deficiency and/or previous cancer treatment in men who were childhood cancer survivors. Men with untreated testosterone deficiency or previous treatment with cranial irradiation were at increased risk of impaired bone health. Prevention of osteoporosis should be considered in their follow-up. Introduction Childhood cancer survivors (CCS) are at increased risk of hypogonadism. Reduced bone mineral density (BMD) has been reported in CCS but it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…CAYA cancer survivors are at increased risk of low BMD (moderate-quality evidence), 6,7,[9][10][11] very low BMD (moderate-quality evidence), 6,7,9,10,[30][31][32][33][34][35][36][37][39][40][41][42][43][44][47][48][49][50][51][52][53][54][55][58][59][60][61][62]64,[66][67][68][69][70][71] and lower BMD Z-scores (moderatequality evidence) after a follow-up period ranging from 2•7 to 27•2 years. 30,31,33,38,39,41,43,<...…”
Section: Risk Of Reduced Bmd and Fracturesmentioning
confidence: 99%
“…CAYA cancer survivors are at increased risk of low BMD (moderate-quality evidence), 6,7,[9][10][11] very low BMD (moderate-quality evidence), 6,7,9,10,[30][31][32][33][34][35][36][37][39][40][41][42][43][44][47][48][49][50][51][52][53][54][55][58][59][60][61][62]64,[66][67][68][69][70][71] and lower BMD Z-scores (moderatequality evidence) after a follow-up period ranging from 2•7 to 27•2 years. 30,31,33,38,39,41,43,<...…”
Section: Risk Of Reduced Bmd and Fracturesmentioning
confidence: 99%
“…Estrogen exerts protective effects on bone (24), and the Tanner stage was the major determinant of BMD in girls (25). Previous studies have also reported that patients with hypogonadotropic hypogonadism had lower BMD compared with normal controls (26). We therefore proposed that low BMD in the lumbar spine and femoral neck in our patient with CED was mostly attributed to the hypogonadism.…”
Section: Mechanism Of Thickened Skull and Cortices Of Diaphysis But L...mentioning
confidence: 71%
“…In this case, the bone alteration can be related to circulating hormones and cytokines produced by the tumor. It is known that patients with primary bone tumors, including osteosarcoma (OS) and Ewing sarcoma, may have bone alteration in the affected sites [ 1 ]. Alternatively, cancer-induced OP can derive from the therapies administered to treat the primary condition.…”
Section: Bone Metabolism and Physiopathology Of Osteoporosismentioning
confidence: 99%
“…Androgens enlarge the cross-sectional area of long bones and increase mechanical strength [ 7 ]. GH and insulin-like growth factor I are important for maintaining bone mass because both independently contribute to bone remodeling and apposition [ 1 ].…”
Section: Bone Metabolism and Physiopathology Of Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation